PENGETAHUAN MASYARAKAT TENTANG PENYAKIT GASTRITIS DI WILAYAH KELURAHAN GEDONG JAKARTA TIMUR - Ida Diana Sari; Fitri Savitri; Rahmat Widiyanto; Agnes Putri Yuanto (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
ABSTRACT Gastritis is inflammation of the mucous lining of the stomach. According to WHO, in Indonesia, the prevalence of this disease is 40.8%. In some regions, it gets quite high, up to 274,396 cases out of 238,452,952 population. Some studies in Indonesia state that among 550 patients undergoing endoscopy procedures, 44% have acute gastritis. One of the causes is helicobacter pylori bacteria. It can also result from other diseases, i.e., the use of the NSAID (Nonsteroidal anti- inflammatory drug), such as aspirin dan ibuprofen, excessive alcohol consumption, cocaine use, physical stress, and smoking habit. This research aims to find out the knowledge of gastritis among the residents of RW 06 Duren Sawit Subdistrict. The method used is a quantitative one. Samples are collected using proportional random sampling with 288 respondents. The data collection is conducted using questionnaires that have been tested for validity and reliability for 50 respondents. The result of the research shows that 215 respondents (75%) have good knowledge, 66 respondents (23%) have moderate knowledge, and 7 respondents (3%) have poor knowledge. It can be concluded that the knowledge of the people of RW 06 Duren Sawit Subdistrict is good. Keywords:Knowledge, Gastritis, Stomach, Proportional Random Sampling